2014
DOI: 10.1136/bjophthalmol-2014-305331
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of choroidal thicknesses using swept source and spectral domain optical coherence tomography in diseased and normal eyes

Abstract: Subfoveal choroidal thickness measurements are comparable between DRI OCT-1 and Spectralis OCT. The presence of retinal disease increases the variability of choroidal thickness measurements between OCT devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
80
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 22 publications
5
80
1
2
Order By: Relevance
“…Three recently published papers have reported this new interesting finding that could extend our knowledge about FUS [1][2][3]. As the authors mentioned in their comments, choroidal thickness has been reported to vary during the course of several inflammatory, and even in non-inflammatory, diseases [4][5][6]. Of course it would be interesting to evaluate choroidal thickness variations occurring between the acute and chronic phase of FUS, and also to correlate choroidal thickness values with the duration of the disease.…”
mentioning
confidence: 62%
“…Three recently published papers have reported this new interesting finding that could extend our knowledge about FUS [1][2][3]. As the authors mentioned in their comments, choroidal thickness has been reported to vary during the course of several inflammatory, and even in non-inflammatory, diseases [4][5][6]. Of course it would be interesting to evaluate choroidal thickness variations occurring between the acute and chronic phase of FUS, and also to correlate choroidal thickness values with the duration of the disease.…”
mentioning
confidence: 62%
“…Previous studies observed a decrease in VEGF expression in the choroid in 1-month-old rats subjected to oxygen-induced retinopathy [26]. While ROP has been shown to cause central and peripheral visual disorder, the exact cause of these deficits is not known [6, 27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…While those studies compared Stratus OCT with Spectralis OCT (Heidelberg Engineering, Heidelberg, Germany), adjustment of segmentation boundaries are possible on the Cirrus OCT. It would be interesting see how the adjusted CST measurements correlate with the reported visual outcomes, and it may be possible to identify other prognostic factors identified for retinal and choroidal imaging [7][8][9], especially with the introduction of swept-source OCT [10].…”
mentioning
confidence: 99%